Design, kinematics, and statics of a novel wave energy converter with parallel mechanism. (13th September 2019) - Chen, Xiulong; Jiang, Deyu
In order to design an ocean wave energy generator robot, a novel wave energy converter with parallel mechanism is designed and analyzed. A creative thinking that parallel mechanism can be applied to the wave energy converter is presented and verified during the wave energy using process. The design principles of the wave energy converter are given according to wave motion characteristics. Based on the principles, a novel wave energy converter with 4UPS/UP parallel mechanism is designed, which includes the design of the parallel mechanism, hydraulic cylinders, oil circuit, and converter integration. Then the kinematics model and statics model of the wave energy converter with 4UPS/UP parallel mechanism are derived by MATLAB and ADAMS; with these two methods, we found that the errors of rod length, velocity, and acceleration were 1.13 mm, 0.04 mm/s, and 0.38 mm/s 2, respectively. Maximum stress error and maximum constraint moment errors were 1.52 N and 0.57 N·mm. So the correctness of the models is verified. This article can not only provide a reference for other types of parallel mechanisms applied to the wave energy converter, but also provide a theoretical foundation for the experimental prototype and practical application of the wave energy converter.